Inclusive Leadership: Good Managerial Practices to Address Cultural Diversity in Schools - Gómez-Hurtado, Inmaculada (2021)
Educational inclusion of foreign pupils has become a priority objective in recent years in many countries worldwide. Attending to the cultural diversity of pupils and providing an inclusive educational response is now a main goal of education systems. In this context, educational leadership is a key factor for school improvement. Management teams face the difficult mission of responding to the diversity of people that make up the educational community in a scenario marked by the expansive increase in migrant families and the scarcity of inclusive and intercultural government programmes. This article explores good management practices for cultural diversity management in six early childhood and primary education centres in Spain and Chile from an inclusive leadership approach. Factors that influence the development of inclusive leadership and the process deployed to carry out diversity management are examined. Through a qualitative methodology, six case studies were carried out using the interview, participant observation, and document analysis as instruments. The main outcomes show the importance of leaders in promoting an inclusive collaborative culture, in classroom practices focused on the knowledge and cultural capital of foreign pupils, the development of organisational and didactic strategies based on the recognition and participation of the educational community, its commitment to social justice, a management of diversity based on collaboration, and a shared concept of educational inclusion. The conclusions show four common dimensions in the good practices of each country: professional development of the community, school participation, inclusive school culture, and positive management of diversity.